Role of microRNA Pathway in Mental Retardation - Abrar Qurashi; Shuang Chang; Peng Jin (The Scientific World Journal)
Deficits in cognitive functions lead to mental retardation (MR). Understanding the genetic basis of inherited MR has provided insights into the pathogenesis of MR. Fragile X syndrome is one of the most common forms of inherited MR, caused by the loss of functional Fragile X Mental Retardation Protein (FMRP).